Influência de variáveis arquitetônicas no desempenho energético de hotéis no clima quente e úmido da cidade de Natal/RN - Lima, Glênio Leilson Ferreira (2007)
This master thesis aims to assess the influence of the design decisions on the energy building performance of hotels. The research is based on the integration of field study and computer simulation. Firstly, a detailed field study is carried out to identify the characteristics of hotels in Natal, Rio Grande do Norte. The items assessed are occupancies, light and equipment densities, types of air conditioning, total and monthly energy consumption, among others. A second and more comprehensive field study is carried out to identify the range of occurrence of architectural variables, with a larger number of buildings. A base case is modelled in VisualDOE, based on the first field study. Then, a first set of simulations are run to explore the sensitivity of the variables on the energy consumption. The results analyses were the base of a second set of simulations, which combined the most influential variables. The results of 384 models were assessed, and the impacts of design decisions were quantified. The study discusses tendencies and recommendations, as well as the methods advantages and disadvantages